Essential orthopaedics including clinical methods - Maheshwari, J.; Mhaskar, Vikram A. (Jaypee Brothers Medical Publishers, 2015)
Essential Orthopaedics is the fifth edition of this highly illustrated resource, ideal for undergraduate revision.Each of the 48 chapters has been thoroughly revised and updated, and an MCQs section has been added to the end of each chapter to aid revision. The chapters begin with a brief review of the relevant anatomy, before discussing basic principles and treatment, with various methods and their indications.